Śrīpaulacaritraṃ = A short life of the Apostle Paul, with a summary of Christian doctrine, as unfolded in his epistles : in Sansktit verse ; with an English version and Bengale and Hindee translations - Muir, John (W.H. Haycock, Bishop's College Press, 1850)
On the life and teachings of Paul, the Apostle, Saint; includes translation in English